2017
DOI: 10.1200/jco.2016.71.0632
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Maintenance Therapy for Women With Low-Grade Serous Cancer of the Ovary or Peritoneum

Abstract: The purpose of this study was to examine outcomes associated with hormonal maintenance therapy (HMT) compared with routine observation (OBS) after primary cytoreductive surgery and platinum-based chemotherapy in women with stage II to IV low-grade serous carcinoma of the ovary or peritoneum. Patients and MethodsEligibility criteria for patients from our database were: treatment with primary surgery followed by platinumbased chemotherapy, stage II to IV disease, at least 2 years of follow-up for patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 39 publications
2
156
0
11
Order By: Relevance
“…Given its relative chemoresistance, some clinicians have abandoned adjuvant chemotherapy in favour of hormonal therapy, whereas others are awaiting results of prospective clinical trials …”
Section: Clinical Course and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Given its relative chemoresistance, some clinicians have abandoned adjuvant chemotherapy in favour of hormonal therapy, whereas others are awaiting results of prospective clinical trials …”
Section: Clinical Course and Treatmentmentioning
confidence: 99%
“…LGSOCs commonly arise in serous borderline tumours (SBOT) and have a high prevalence of BRAF (0–33%, average 5%) and KRAS (19–55%) mutations, with research suggesting NRAS mutations may be an oncogenic driver in their progression . LGSOCs have greater expression of oestrogen receptors (ER) and progesterone receptors (PR) and are typically TP53 wild‐type . Cumulative research suggests a role of the mitogen‐activated protein kinase (MAPK) pathway in their pathogenesis and there is growing evidence regarding targeted agents in management …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormone antagonistic therapy has demonstrated significant benefit in prolonging time to disease progression in retrospective studies 11. However, respondents in this survey did not commonly elect to use hormone antagonism as consolidation therapy after primary treatment with no evidence of disease.…”
Section: Discussionmentioning
confidence: 87%
“…LGSCs commonly express estrogen (ER) and progesterone receptors (PR). A retrospective study has shown benefit of antiestrogens in the adjuvant setting . Another case series demonstrated response to bevacizumab .…”
Section: Nonepithelial Cancersmentioning
confidence: 99%